Introduction. - TUBAU, XAVIER (Renaissance & Reformation / Renaissance et Réforme, 2019)
An introduction is presented in which the editor discusses articles in the issue on topics including the reassessment of early modern Spanish catholicism, the church and the reduction of papal power, and the history of constitutionalism, the Gallican Church and the Protestant Reformation.